GAZ NÍZAMLARÍN GAZLÍ TERMOMETR JÁRDEMINDE ÚYRENIW - Jalelov, M.A.; Otarbaev, A.E.; Jaksimuratov, I.J. (ILIM hám JÁMIYET, 2021)
This article the discusses the methods for studying ideal gas laws. Emphasizing the importance of studying the laws of Charles and Boyle-Marietta using a gas thermometer and the expected results.
Keywords: gazlı termometr; Mobile CASSY lab; turg’un hajm; doimiy harorat; simob tomchisi; ortiqcha bosim; dastakli vakuum nasosi